Exploring Online and Offline Factors Influencing Employee Motivation and Performance in Iraqi SMEs - Zaidan, Muslim N.; Hamza, Ahmad H.; Hamdi, Sameer S.; Awqati, Ali J. (Mağallaẗ ğāmiʻaẗ Ğīhān- Arbīl li-l-ʻulūm al-insāniyyaẗ wa-al-iğtimāʻiyyaẗ, 2025)
This study examines the impact of online and offline factors on employee productivity and performance within the SME enterprises in Iraq. The study aims to evaluate how digital tools, training, remote work, and communication platforms as an online factor, as well as work environment, leadership, team dynamics, and physical conditions as an offline factors, influence employee performance. Additionally, the role of employee motivation as a mediating factor between these factors. A quantitative methodology was utilized, gathering data from 180 employees of SMEs across several sectors in Baghdad and Erbil using a structured survey. This sample encompasses many divisions within the SME sector, reflecting a comprehensive overview of employee viewpoints regarding elements influencing motivation and performance. The analysis is conducted using Smart PLS to test the structural equation model (SEM), assessing both direct and indirect relationships. The finding shows online and offline factors have significant effect on on employee motivation and performance, while the two indirect hypotheses showed a mediating effect of employee motivation on the relationship between workplace factors and employee performance. The findings are expected to provide insights into how online and offline workplace factors, along with employee motivation, contribute to overall employee performance in Iraq's working in SME enterprises, offering valuable recommendations for improving productivity and efficiency in the industry and in the context of Iraqi enterprises